Study of Nail Psoriasis and Dermoscopic Correlation With Dermoscopic and Modified Dermoscopic Nail Psoriasis Severity Indexes (dNAPSI and dmNAPSI) - Arora, Sandeep; Paul, Debatraya; Kumar, Richa; Bhatnagar, Anuj; Arora, Gulhima; Mech, Sunita; Kumar Suhag, Devinder (Dermatology Practical & Conceptual, 2022)
Background: Nail involvement in psoriasis may be assessed clinically, ultrasonologically, and dermoscopically. The aim of this study was to assess the dermoscopic features of nails in psoriasis, compare them with clinical findings, and correlate them with the Nail Psoriasis Severity Index (NAPSI) score.Methods: We recruited 120 patients with psoriatic nail changes for the study. The Psoriasis Area Severity Index (PASI) was used to assess the severity of disease. Clinical and dermoscopic (DermLite DL4, ×10, polarized and non-polarized) nail examination determined NAPSI, modified NAPSI (mNAPSI), and NAPSI determined with dermoscopic findings (dermoscopic NAPSI [dNAPSI] and dermoscopic modified NAPSI [dmNAPSI]) were used to assess severity of nail involvement.Results: Subungual hyperkeratosis (50.8%) and nail plate thickening (56.7%) were the commonest clinical nail changes found, and dermoscopically, they were subungual hyperkeratosis and pitting (68.3% each). The average median with interquartile range of PASI and NAPSI scores were 7.5 [5.7-10.8] and 8.0 [6-12], respectively. NAPSI scores increased significantly with the increase in PASI scores (P < 0.001). A comparison of NAPSI and mNAPSI with dNAPSI and dmNAPSI revealed that NAPSI, mNAPSI, and dNAPSI increased significantly with an increase in PASI scores. dNAPSI scores increased significantly with increased mNAPSI and dmNAPSI, and mNAPSI and dmNAPSI were significantly good predictors of joint involvement in psoriasis.Conclusions: Dermoscopy allows for better visualization of nail findings. Evaluating NAPSI and mNAPSI scores in conjunction with dNAPSI and dmNAPSI increases their helps detect early psoriasis, detection of worsening moderate-to-severe psoriasis (PASI >10) and predict joint involvement and their severity